Limb Ischemic Necrosis Secondary to Microvascular Thrombosis: A Brief Historical Review - Warkentin, Theodore E. (Seminars in Thrombosis and Hemostasis, 2024)
Ischemic limb injury can be broadly classified into arterial (absent pulses) and venous/microvascular (detectable pulses); the latter can be divided into two overlapping disorders—venous limb gangrene (VLG) and symmetrical peripheral gangrene (SPG). Both VLG and SPG feature predominant acral (distal) extremity ischemic necrosis, although in some instances, concomitant nonacral ischemia/skin necrosis occurs. Historically, for coagulopathic disorders with prominent nonacral ischemic necrosis, clinician-scientists implicated depletion of natural anticoagulants, especially involving the protein C (PC) system. This historical review traces the recognition of natural anticoagulant depletion as a key feature of nonacral ischemic syndromes, such as classic warfarin-induced skin necrosis, neonatal purpura fulminans (PF), and meningococcemia-associated PF. However, only after several decades was it recognized that natural anticoagulant depletion is also a key feature of predominantly acral ischemic microthrombosis syndromes—VLG and SPG—even when accompanying nonacral thrombosis is not present. These acquired acral limb ischemic syndromes typically involve the triad of (a) disseminated intravascular coagulation, (b) natural anticoagulant depletion, and (c) a localizing explanation for microthrombosis occurring in one or more limbs, either deep vein thrombosis (helping to explain VLG) or circulatory shock (helping to explain SPG). In most cases of VLG or SPG there are one or more events that exacerbate natural anticoagulant depletion, such as warfarin therapy (e.g., warfarin-associated VLG complicating heparin-induced thrombocytopenia or cancer hypercoagulability) or acute ischemic hepatitis (“shock liver”) as a proximate factor predisposing to severe depletion of hepatically synthesized natural anticoagulants (PC, antithrombin) in the setting of circulatory shock.
Keywords: acute ischemic hepatitis (“shock liver”); disseminated intravascular coagulation; heparin-induced thrombocytopenia; natural anticoagulants; symmetrical peripheral gangrene; venous limb gangrene